The mechanism of artemisinin resistance of Plasmodium falciparum malaria parasites originates in their initial transcriptional response - Zhu, L; Pluijm, RVD; Kucharski, M; Nayak, S; Tripathi, J; Nosten, F; Faiz, A; Amaratunga, C; Lek, D; Ashley, E; Smithuis, F; Phyo, AP; et al. (bioRxiv, 2021)
The emergence and spread of artemisinin resistant Plasmodium falciparum , first in the Greater Mekong Subregion (GMS), and now in East Africa, is a major threat to global malaria eliminations ambitions. To investigate the artemisinin resistance mechanism, transcriptome analysis was conducted of 577 P. falciparum isolates collected in the GMS between 2016–2018. A specific artemisinin resistance-associated transcriptional profile was identified that involves a broad but discrete set of biological functions related to proteotoxic stress, host cytoplasm remodeling and REDOX metabolism. The artemisinin resistance-associated transcriptional profile evolved from initial transcriptional responses of susceptible parasites to artemisinin. The genetic basis for this adapted response is likely to be complex.